KERJASAMA AMERIKA SERIKAT DAN THAILAND DALAM MENANGANI KASUS SLAVERY AND HUMAN TRAFFICKING DI INDUSTRI PERIKANAN THAILAND 2013-2017 - Habeahan, Peri Anda; Utomo, Tri Cahyo (Journal of International Relations, 2018)
Slavery and Human Trafficking in Thailand is one of a transnational crimes that growing rapidly. According to Interpol data in 2009, this global fenomena is often happen especially in under-developed countries. This case was caused by globalization, broker’s chain, low law enforcement, government involvement in corruption cases that took profit of this humanity crimes. This case had caused the migrants of Cambodia, Myanmar and Laos were sold in order to work in Thailand fishing industry sector. They had physical violence from the boad owner and crew, even among them have became murder victims. Forced kidnap, violence fraud on the boad and port caused all the migrants tried their best to e escape. This case became a challenge for United States as one of Thailand’s partner in seafood export sector. International pressure from media, NGOs and international organizations were concerned on and asked US and Thailand to take decitions and policies. This research is aim to know the cooperation of these two countries in addressing the slavery and human trafficking case in Thailand’s fishing industry in 2013-2017. This research type is descriptive-explanative by qualitative data analysis technique by literature data collection. This research result is explanation of government’s policy of United States and Thailand in addressing the slavery and human trafficking in Thailand, through aid program of USAID and Bureau of Democracy, Human Rights and Labor (DRL) with many program’s implementation, collaboration and cooperation on corruption handling.